A note on East Australia Group V Stock humpback whale movement between feeding and breeding areas based on photo-identification - Rock, J.; Pastene , L. A.; Kaufman , G.; Forestell , P.; Matsuoka, K.; Allen, J. (J. Cetacean Res. Manage., 2023)
Documentation of humpback whale migratory movements between Australasia and the Southern Ocean has been limited almost exclusively to historical whaling data. This study examines photographic evidence documenting the movements of three individual humpback whales between their breeding grounds on the northeast coast of Australia and feeding grounds in Area V of the Southern Ocean. Although these individuals exhibited marked site fidelity to the same low latitude breeding grounds, their sightings in high latitude feeding grounds vary by 35° longitude, confirming dispersal of Eastern Australia Group V Stock humpback whales in the Antarctic feeding ground.